Exogenously applied growth promoters modulate the antioxidant enzyme system to improve the cotton productivity under water stress conditions - Hussain, Nazim; Yasmeen, Azra; Afzal, Muhammad Ahsan (Italian Journal of Agronomy, 2020)
Great climatic inconsistency and increased frequent occurrences of severe conditions results in plants being exposed to water stress at various growth stages, thus adversely affecting the productivity. This investigation was planned to minimize the water stress induced-losses to cotton plants with the exogenous application of growth promoters i.e. distilled water, salicylic acid (0.5 mM), jasmonic acid (50 Î¼M) and moringa leaf extract (MLE30) including control (un sprayed). Cotton plants were exposed to water stress with the application of irrigation water at 10 (well-watered) and 30 day intervals (severe water stress). Results indicated that water stress severely reduced the cotton productivity. It was observed that exogenous application of salicylic acid and moringa leaf extract improved the productivity both under well-watered and water stress conditions as compared to other treatments. However, exogenous application of salicylic acid had greater influence on the studied parameters than MLE, although the insignificant differences were documented in most of the traits. Exogenous application of salicylic acid reduced the cell injury percentage, improved the cell membrane thermostability and produced significantly higher content of leaf protein, superoxide dismutase (SOD), peroxidase (POD) and catalase (CAT) that modulated the negative influence of water stress on yield contributing attributes and produced maximum seed cotton yield. These results indicate that exogenous application of SA and MLE helped the cotton plants to become more tolerant to water stressinduced losses by adjusting the membrane characteristics and improving their antioxidant defence mechanism.